Alterações no estoque e taxa de sequestro de carbono em um Latossoto vermelho submetido a sistemas de manejo. - Santos, Josiane Bürkner dos (2006)
The objective of this study was to quantify the changes of the total carbon (C) and total nitrogen (N) stock, and the variation of the C pool’s in monthly soil samples, and the C balance and C sequestration rates provoked by the soil tillage systems. The soil samples were accomplished in a long term experiment implanted in 1988, in the experimental station of Fundação ABC located in Ponta Grossa city, Center-South area of the Paraná State. The soil tillage systems were comprised: a) Conventional Tillage (CT); b) Minimum Tillage (MT); c) No-tillage with chisel plow (NTCP) each three years; and d) No-tillage – Continuous (NTC). Soil samples for each treatments were obtained by digging 3 profiles of 20-cm x 50-cm (surface area) x 50-cm deep for each replicate, and collected from three depths (0,0- to 2.5- cm, 2.5- to 5-cm, 5- to 10-cm). In the samples collected in October of 2003, May of 2004 and November of 2004, the total organic carbon (TOC) and the total nitrogen in all of the depths was measured. The particle size fractionation was accomplished, separating the soil in fractions in the size of 2000 - 210 Wm, 210 - 53 Wm and <53 Wm. In all these fractions TOC was determined. The treatments had significant effects on TOC and TN contents and pools. The total C and N stock in NTC was superior to the other systems demonstrating larger maintenance of C in the soil. The larger concentration of C was observed in the 210 to 53 Wm particle size fraction in the NTC. In the 2000 - 210 Wm fraction of the 0,0-2,5 cm layer were observed larger changes in the C stock due to the management systems in the samples at all long year. The greatest change was accomplished to CT. In NTP, the stock of C was larger in all soil samples, indicating that the maintenance of the cultural residues in the associated surface protection of the aggregates allows larger accumulation of C. Although the C stock in the particle size fraction <53 Wm not to present significant differences among the management systems, and was observed the C migration of the coarse fractions (210-53 and 2000-210 Wm) to the recalcitrant particle size fraction, indicating a continuous C flow. The C balance model adjusted for the local conditions revealed that the oxidation rate acted by K2 is inferior to the simulations accomplished by other authors, demonstrating the importance of the local conditions. With this model, the minimum amount of crop residues to maintain NTC system in steady-state was 8,05 Mg ha-1 year-1 while in the PC treatment it won't be possible to reach the balance with the amount of crop residues placed in this long term experiment, being a deficient system.